Silence Speaks: An Exploratory Study of Underlying Motives of Non-Complaining Customers - Iram , Faria; Bakar, Abou; Ali, Asad (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this article is the exploration of the underlying motives of customer’s non-complaining behavior. We have used critical incident technique to investigate those factors. In our study, non-complainers are identified as the individuals who do not raise their voice against product/service failure. We came across eight main themes and twenty sub-themes to as the reason behind for indulging in non-complaining behavior. Religion specific theme is the only theme which was diverging from the previous literature. This study proposes some important implications for managers in helping them to retain loyal customers by accommodating their concerns. This study holds importance as that most of the studies are carried out in the Western context and a very little research has been done in developing countries like Pakistan.